If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(1 + 4x) = -4x + -5 (1 * -3 + 4x * -3) = -4x + -5 (-3 + -12x) = -4x + -5 Reorder the terms: -3 + -12x = -5 + -4x Solving -3 + -12x = -5 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -3 + -12x + 4x = -5 + -4x + 4x Combine like terms: -12x + 4x = -8x -3 + -8x = -5 + -4x + 4x Combine like terms: -4x + 4x = 0 -3 + -8x = -5 + 0 -3 + -8x = -5 Add '3' to each side of the equation. -3 + 3 + -8x = -5 + 3 Combine like terms: -3 + 3 = 0 0 + -8x = -5 + 3 -8x = -5 + 3 Combine like terms: -5 + 3 = -2 -8x = -2 Divide each side by '-8'. x = 0.25 Simplifying x = 0.25
| 7x+49=2x+49 | | -5x=9-y | | 2L^2-6L-20=0 | | 3x-4-16=2x-16+7 | | u^2=144 | | 5m+7=4m+12 | | 120=1/2[(360-X)-x] | | -3x-7*0=21 | | Y+1=7(x+3) | | x=4ln(10)-4ln(5) | | -5e^2x=25 | | x=4ln(5) | | 7.56x+25=57.1536+5x | | 2x-(-x-3)=-2x-3 | | 8a+2=6a-8 | | kx^2-26x+51=0 | | 54=-6(3x+18) | | 5x-5=4x-13 | | 20=2x-3(4x+10) | | (x)3/32=54 | | [(x+10)-24]+(x+10)+x=180 | | -2-2x-5=-x-3(x-1) | | y-23=9 | | -5.8(3t+5)-2.5(2t-6)= | | 5x-2(-2y+4x)-5y= | | log(3x-2)5=3 | | -5t^2+20t-25=0 | | 100[0.06(z+3)]= | | 360=25-2+20x-1 | | 2x=8x-43 | | 2x^2-x=x | | 4x-40+6x=180 |